2013
DOI: 10.2489/jswc.68.4.270
|View full text |Cite
|
Sign up to set email alerts
|

Greening summer fallow with legume green manures: On-farm assessment in north-central Montana

Abstract: Replacing summer fallow practices with annual legumes as green manures (LGMs) may increase the sustainability of northern Great Plains wheat (Triticum aestivum L.) systems. Viability hinges on soil water use management and realizing biologically fixed nitrogen (N) benefits. Plot-scale research has shown that managing LGMs with first-flower stage termination and no-till practices conserves soil water and that rotational N benefits can increase wheat grain quality. Nonetheless, farmer adoption of LGMs has been n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 57 publications
5
37
0
1
Order By: Relevance
“…By managing soil water use conservatively and for multiple rotations, lentil green manure in tilled systems increased soil N contributions to spring wheat in northeastern Montana (Pikul et al, 1997;Allen et al, 2011) and was found to be economically profi table in southwestern Saskatchewan (Zentner et al, 2004). Miller et al (2006) showed similar promise with chemically killed pea manure in sequence with spring wheat in a notill system in north central Montana but subsequent cropping sequence work showed that wheat yield and protein responses to pea manure were inconsistent (Miller et al, 2011;O'Dea et al, 2013;Burgess et al, 2014). Th e objective of this study was to compare crop yield and quality parameters and net returns among six 4-yr pea-wheat and wheat-only crop rotations in southwestern Montana.…”
mentioning
confidence: 85%
“…By managing soil water use conservatively and for multiple rotations, lentil green manure in tilled systems increased soil N contributions to spring wheat in northeastern Montana (Pikul et al, 1997;Allen et al, 2011) and was found to be economically profi table in southwestern Saskatchewan (Zentner et al, 2004). Miller et al (2006) showed similar promise with chemically killed pea manure in sequence with spring wheat in a notill system in north central Montana but subsequent cropping sequence work showed that wheat yield and protein responses to pea manure were inconsistent (Miller et al, 2011;O'Dea et al, 2013;Burgess et al, 2014). Th e objective of this study was to compare crop yield and quality parameters and net returns among six 4-yr pea-wheat and wheat-only crop rotations in southwestern Montana.…”
mentioning
confidence: 85%
“…Positive rotational effects of pulses to subsequent cereal or oilseed crops have been well documented in Mediterranean-type climates 52 . However, the findings on the rotational benefits of pulses in the short-season, semiarid northern latitudes have been inconsistent 49,[53][54][55][56] . In particular, it is unclear in the scientific literature whether the beneficial features that are associated with conventional summerfallowing can be retained with improved, pulse-based systems in water scarce environments.…”
Section: Discussionmentioning
confidence: 99%
“…This delayed response may be a reality of cool, waterlimited conditions in the NGP leading to low annual legume biomass contributions, slow breakdown of residues, and subsequent slow release of available N (Janzen et al 1990;Bremer and van Kessel 1992;Beckie et al 1997), especially in no-till systems (Schoenau and Campbell 1996;Triplett and Dick 2008). A lack of immediate benefits is potentially discouraging to producers expecting N fertilizer-type responses from legumes (O'Dea et al 2013) while a more reasonable expectation may be a gradual buildup of the soil N pool (Ladd et al 1981;Janzen et al 1990). …”
Section: Introductionmentioning
confidence: 99%
“…Legumes are assumed to provide N benefits to subsequent wheat, but this is not consistently detected in primarily short-term studies from the NGP (Miller et al 2002;Lupwayi and Kennedy 2007;O'Dea et al 2013). Longer-term studies suggest that N-benefits to wheat may be realized only after multiple years of legumes in rotation (Campbell et al 1992;Zentner et al 2004;Walley et al 2007;Allen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation